Interactions Between Generations in Digital Literacy Education: A Case of Millennial Families in Suli, Central Maluku - Latuheru, Markus Silfanus; Manuputty, Feky; Angkotasan, Sulaiman (Baileo: Jurnal Sosial Humaniora, 2024)
This study explores intergenerational dynamics in digital literacy education within millennial families in Suli Village, Central Maluku. The research aims to understand how intergenerational interaction facilitates the transfer of digital competencies and cultural values, positioning millennial family members as digital literacy facilitators and baby boomers as sources of ethical and traditional wisdom. Employing a structured descriptive qualitative approach, data were gathered through interviews, participant observation, and documentation analysis to uncover the nature, challenges, and potentials of digital learning across generations. Findings indicate that millennials play a transformative role in introducing and guiding older family members—particularly baby boomers—through the digital landscape. In turn, baby boomers contribute by reinforcing values related to digital responsibility and cultural ethics. This reciprocal relationship not only strengthens family cohesion but also promotes adaptive digital behaviors across age groups. Moreover, the research underscores the pivotal role of schools in shaping critical digital literacy among youth and the potential of community-based initiatives to bridge generational gaps in digital understanding. The novelty of this study lies in its contextual focus on millennial families in a rural Indonesian setting and the integration of cultural values into digital education. By framing digital literacy as both a technical and socio-cultural competency, the study contributes to the advancement of social and human sciences. It recommends the development of intergenerational digital literacy campaigns involving families, schools, and community actors as a strategic approach to foster inclusive and sustainable digital literacy in local contexts.